The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1111/j.1440-1738.2009.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry of the Zargoli granite: Implications for development of the Sistan Suture Zone, southeastern Iran

Abstract: The Zargoli granite, which extends in a northeast-southwest direction, intrudes into the Eocene-Oligocene regional metamorphic flysch-type sediments in the northwest of Zahedan. This pluton, based on modal and geochemical classification, is composed of biotite granite and biotite granodiorite, was contaminated by country rocks during its emplacement, and is slightly changed to more aluminous. The SiO 2 content of these rocks range from 62.4 to 66 wt% with an alumina saturation index of Shand [molar Al 2 O 3 / … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 68 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…Biostratigraphic data suggest that the Sistan oceanic basin formed in Early Cretaceous time [ Babazadeh and De Wever , ]. Ages of high‐pressure rocks of ~89–78 Ma suggest that subduction of the Sistan Ocean occurred in Late Cretaceous time [ Bröcker et al ., ], but collision‐related granitoids as young as late Oligocene are interpreted to result from collision‐related lithosphere removal [ Rezaei‐Khakhaei et al ., ] and may indicate that shortening continued well into the Cenozoic. Middle Miocene volcanics (14–11 Ma) are only weakly deformed and postdate significant E‐W shortening [ Pang et al ., ].…”
Section: Restoring the Cenozoic Nw India/kabul Block—asia Collisionmentioning
confidence: 99%
“…Biostratigraphic data suggest that the Sistan oceanic basin formed in Early Cretaceous time [ Babazadeh and De Wever , ]. Ages of high‐pressure rocks of ~89–78 Ma suggest that subduction of the Sistan Ocean occurred in Late Cretaceous time [ Bröcker et al ., ], but collision‐related granitoids as young as late Oligocene are interpreted to result from collision‐related lithosphere removal [ Rezaei‐Khakhaei et al ., ] and may indicate that shortening continued well into the Cenozoic. Middle Miocene volcanics (14–11 Ma) are only weakly deformed and postdate significant E‐W shortening [ Pang et al ., ].…”
Section: Restoring the Cenozoic Nw India/kabul Block—asia Collisionmentioning
confidence: 99%
“…We do not reconstruct the western margin of the collision zone in Afghanistan and Pakistan because there is a general absence of kinematic data. We note, however, that there is evidence for Cenozoic extrusion of the Afghan Block westward along the conjugate Helmand and Chaman strike‐slip faults [ Tapponnier et al , 1981], and E‐W closure of the Sistan ocean between the Afghan Block and the Lut Block in eastern Iran, which perhaps continued until Oligocene‐Miocene times [ Rezaei‐Kahkhaei et al , 2010] (Figure 2). Given the kinematics of the known major faults and the E‐W compression in eastern Iran, restoring this region would probably indicate some westward lateral escape of the Afghan Block.…”
Section: Reviewmentioning
confidence: 99%
“…It has been suggested that during the initial collision of an orogenic wedge with a continent, major compressional stresses can be transmitted into the continent as a consequence of subduction resistance, giving rise to large-scale intraplate deformations and strike-slip shear zones (Ziegler, van Wees & Cloetingh, 1998; Rezaei-Kahkhaei et al . 2010). Similarly, Triassic collisional orogenesis of the Qinling Orogen produced intensive brittle-ductile shearing deformation and greenschist-facies metamorphism in the WQO (Zhang et al .…”
Section: Discussionmentioning
confidence: 99%